Novel tuffite/Fe-Cu oxides nanocomposite with functionality for dye removal in aqueous solution. Issue 4 (December 2016) - Blanco-Flores, Alien; Sánchez-Mendieta, Victor; Gutiérrez-Segura, Edith; Vilchis-Néstor, Alfredo R.; Morales-Luckie, Raul A.
Graphical abstract: Highlights: We developed the novel and inexpensive adsorbent material tuffite/Fe-Cu oxides nanostructures composite. This nanocomposite exhibits high adsorption capacity for removing Malachite Green (MG) as a cationic-dye model. Kinetics, thermodynamics and isotherm of the adsorption process were comprehensively studied. MG adsorption kinetics followed a pseudo-first order kinetic model. Kinetic and thermodynamic studies evidenced physisorption as the main process. Abstract: Fe-Cu oxides nanoparticles were embedded on tuffite (TUF) mineral by means of a simple immersion-ion impregnation, followed by a reduction reaction, methodology. TUF/Fe-Cu nanocomposite characteristics were investigated by XRD, TEM, BET, SEM, FT-IR spectroscopy and pHzpc method. Fe-Cu nanostructures with mean sizes between 10 and 20 nm were effectively supported on TUF. Because of its functional properties, the nanocomposite was studied as adsorbent material for the degradation of malachite green (MG) organic dye in aqueous solution. The adsorption kinetic data was well-fitted to pseudo first-order model, indicating physisorption as the main mechanism of adsorption. High pH and temperature of the solution favored malachite green adsorption. The adsorption process was spontaneous and endothermic. In comparative sorption experiments with different dyes, the nanocomposite showed better removal capacities for cationic and basic than for anionic and acid dyes. Langmuir, Freundlich, Langmuir-Freundlich and Temkin models were applied to evaluate the isotherms, resulting in an adsorption capacity of 376.66 mg/g, which is above most of the adsorbent materials so far employed for malachite green degradation in aqueous solution. Therefore, this novel, easy to prepare and low-cost nanocomposite proved to have synergic functionality as an efficient adsorbent material for cationic organic dyes.